Nurses' Experiences in Management of Occupational Safety Action: A Qualitative Study - Sartika, Dewi; Awaludin, Sidik; Rusdi, Ibnu (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background. Nurses are at a high risk of exposure to hazards that threaten their health and safety. Effective nurse occupational safety management is crucial for ensuring nurse safety and improving shared healthcare services. However, nurses' experiences in managing occupational safety measures have not been widely explored. Therefore, this study aims to explore nurses' experiences in occupational safety management. Methods. A qualitative study with an interpretative descriptive approach was conducted. A total of 14 nurses working in a hospital in Pekanbaru City were invited to contribute. The sample was collected by a purposive sampling technique. Data collection employed a focus group discussion method, utilizing open-ended questions. The data were analyzed using Collaizi strategies. Results. Most of the participants indicated more than 10 years of work experience. The majority of the educational background was Ners. Four main themes were generated, namely the perception of occupational safety action, the efforts in occupational safety action, the barriers in occupational safety action, and the factors influencing nurses' implementation of occupational safety action. Conclusion. The participants had valuable experiences and ideas that should be considered by nurse leaders in improving the occupational safety action management in the hospital. Nurse managers, particularly head nurses, are expected to optimize their roles and functions in managing occupational safety action through direction, motivation, reminders, and supervision. Hospital management is advised to provide all facilities and also needs to improve the safety culture among nurses to support occupational safety action.